Striving for smoke-free families: Wives’ role in Gayo Lues, Aceh-Indonesia - Saffutra, Hasrizal; Yahya, Mustanir; Rosemary, Rizanna; Indah, Rosaria; Syahrizal, Dedy (Narra J, 2025)
Smoking remains a prevalent habit in many households, particularly in regions where cultural norms strongly accept tobacco use. The aim of this study was to examine the influential role of wives in Gayo Lues, Aceh, Indonesia, in promoting smoking cessation within their families. Amidst cultural norms that widely accept smoking, these wives employed both persuasive and, occasionally, coercive methods to encourage healthier behaviors among family members. Utilizing a qualitative approach with Participatory Action Research (PAR), data were collected through in-depth interviews with seven wives who have firsthand experience with smoking behaviors in their families. The findings revealed that wives in Gayo Lues act as both health monitors and guardians, balancing emotional support with firm boundaries to foster a smoke-free home environment. Their roles extended beyond traditional caregiving, as they actively shape family health outcomes. In conclusion, this study underscored the importance of empowering wives as health advocates in public health efforts, particularly in culturally conservative settings. Future research could further explore the broader socio-cultural dynamics influencing wives’ health advocacy roles and assess the sustainability of these behaviors over time.